(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article explores the relationship between gender and language, focusing on how linguistic differences reflect societal roles and power dynamics. The study also delves into nonverbal communication, such as intonation, gestures, and body language, which further differentiate male and female speech. Through examples from both English and Uzbek languages, the article demonstrates how linguistic expressions and cultural norms shape gendered communication and influence social interactions.